Antibiofilm and anticancer potential of β-glucan-binding protein-encrusted zinc oxide nanoparticles. (April 2020) - Divya, Mani; Govindarajan, Marimuthu; Karthikeyan, Sivashanmugam; Preetham, Elumalai; Alharbi, Naiyf S.; Kadaikunnan, Shine; Khaled, Jamal M.; Almanaa, Taghreed N.; Vaseeharan, Baskaralingam
Abstract: β - Glucan-binding protein (βGBP) is important for the rational expansion of molecular biology. Here, zinc oxide nanoparticle (ZnONP) was synthesized using βGBP from the crab Scylla serrata (Ss-βGBP-ZnONP). Ss-βGBP-ZnONP was observed as a 100 kDa band on sodium dodecyl sulfate polyacrylamide gel and characterized with UV–vis spectroscopy at 350 nm. X-ray diffraction analysis displayed values consistent with those for zincite. Fourier transform infrared spectroscopy revealed the presence of functional groups, including amide, alcohol, alkane, alkyl halide, and alkene groups. The zeta potential (−5.36 mV) of these particles indicated their stability, and transmission electron microscopy revealed the presence of 50 nm nanocones. Ss-βGBP-ZnONPs were tested at 100 μg/mL against the gram-positive Enterococcus faecalis and gram-negative Pseudomanas aeruginosa using confocal laser scanning microscopy and the bacterial viability assay was also performed. The growth of MCF7 breast cancer cells was inhibited following treatment with 75 μg/mL Ss-βGBP-ZnONPs. Thus, Ss-βGBP-ZnONPs have the ability to control the growth of pathogenic bacteria and inhibit the viability of MCF7 breast cancer cell lines. Graphical abstract: Image 1 Highlights: β-Glucan-binding protein-coated ZnONPs was synthesized from Scylla serrata . Ss-βGBP-ZnONPs was characterized with UV, XRD, FTIR, zeta potential, and TEM. Inhibition of biofilms by Ss-βGBP-ZnONPs was confirmed at 100 μg/mL. Ss-βGBP-ZnONPs at 75 μg/mL effectively inhibited MCF7 breast cancer cells.